Nominee Agreements as Instruments of Fraud in Educational Foundations : Criminal Responsibility of Foundation Organs for Misappropriating Land Assets Ownership - Michael Giovanni Joseph; Handoyo Prasetyo; Heru Sugiyono (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
This study examines the use of nominee agreements as instruments of fraud within Indonesian foundations that operate private educations. This research focuses on how foundation organs use the foundations to buy land assets for themselves and evade liability. The problem addressed is the gap between civil‐law façade and underlying criminal intent, whereby Patrons, Management, and Supervisors transfer land ownership out of the foundation’s name through a simulated agreement called nominee contracts. The research aims to analyze how these contracts facilitate systemic fraud and to propose a legal framework for holding both individuals and the foundation itself criminally accountable. A doctrinal‐normative method is employed, involving analyses of statutory provisions (Foundation Law, the old and the new Criminal Code), internal regulations, and key court decisions (e.g., Gunung Muria University, Al‐Hilaal Ambon, Morning Star). Findings reveal that nominee agreements consistently conceal intent to defraud, that existing legal provisions are underutilized or applied piecemeal, and that criminal courts have been reluctant to dissolve offending foundations despite clear evidence of strafbaarfeit (criminal act) by the foundation. The main synthesis highlights the necessity of a consistent approach by the law enforcement and the court to interpret nominee‐based transfers as criminal acts to prevent further asset diversion. The study concludes that integrating civil and criminal frameworks, along with strengthening oversight and enabling immediate dissolution of fraudulent foundations, is essential to safeguard public interest and restore trust in the nonprofit sector.